Macroplastics in the environment: are they suitable habitats for macroinvertebrates in riverine systems? - Ali, Andrew Abagai (Rhodes University, Faculty of Science, Institute for Water Research)
Emerging pollutants, such as plastics are threat to freshwater ecosystems, and may negatively impact riverine systems. They can modify riverine habitats and affect aquatic organism distribution and composition. Knowledge of how macroplastics alter riverine habitat heterogeneity, and their effects on macroinvertebrate assemblage structure is sparse, especially in Africa. This study examines the effect of hydraulic biotopes on the colonisation, establishment and succession patterns of macroinvertebrates on macroplastic and natural substrates based on the taxonomic and trait-based approach. Four experimental sites from minimally impacted upper reaches of the Buffalo, Kat, Kowie, and Swartkops Rivers in the Eastern Cape of South Africa were selected for the deployment of plastic substrates. Plastics materials, including polyethylene terephthalate (PET) bottles and natural substrate composed of stone and vegetation, were used to formulate three substrate groups: Group 1: 100% natural substrates (NS), Group 2: 50% natural substrates and 50% plastic material (NP), and Group 3: 100% plastic materials (PD). These substrates were placed in litter bags of equal dimension (25 cm by 35 cm, with 2.5 cm mesh) and deployed randomly in three hydraulic biotopes (pools, riffles, runs) over a period of 180 days (October 2021 to April 2022). A total of 216 substrate bags, 54 bags per substrate were deployed per site in the four experimental sites. Twelve bags from each substrate group were retrieved at an interval of 30 days beginning on day 30 after deployment, and analysed for the establishment of macroinvertebrate communities. Based on composite hydraulic biotope data, Simpson index was significantly higher (P < 0.05) for macroinvertebrate assemblage structure on the 50% and 100% macroplastic substrate groups compared to natural substrates. With the exception of Tabanidae, Glossosomatidae, and Psephenidae, all macroinvertebrate taxa recorded showed non-significant positive correlations with all three substrate groups. However, Tabanidae, Glossosomatidae, and Psephenidae showed significant positive correlation with the 100% natural substrates, 50% plastic substrates and 100% plastic substrates, respectively. The parsimony analysis reveal that, within 30 days, all substrate groups underwent similar succession, with high abundance of pioneer taxa which increased on days 60 and 90, and then decreased from days 120 to 180. For the the pool biotope, Shannon and Simpson indices were significantly higher (P < 0.05) for the macroinvertabrates collected over the natural substates compared with those collected on the macroplastic substrate groups. However, in the riffle and run biotopes, all diversity indices were similar for all substrate groups and no statistically significant difference was observed. Statistically significant higher values for taxonomic richness, diversity, and evenness were found on day 30 to 90 for the riffle biotopes, and day 30 to 60 for the run biotopes. The run biotope presented temporal statistical significant variability in taxonomic composition with different macroinvertebrate communities recorded on days 30 and 60 compared with days 90 to 180. However, in pools and riffles, no temporal variation was observed in the taxonomic composition of macroinvertebrates on all three substrate groups. The trait-based fuzzy correspondence analysis revealed differential spatial-temporal distribution of macroinvertebrate traits on all three substrate group. The early colonisers i.e. day 30 "“ 60, were dominated by group of taxa characterised by medium (>10 "“ 20 mm) and large (20 > 40) body size, flat body, collector-gatherers, free-living, and predators. The late colonisers, collected mainly on day 150 and 180 were dominated by taxa with a preference for high flow velocity (0.3 - 0.6 m/s), permanent attachment, and filter-feeding mode. Traits such as oval and flat body shape, medium body size (>10 - 20 mm), skating and clinging/climbing mobility, temporal attachment, shredders, predators, prey, and plastron and spiracle respiration showed positive correlation with the 100% macroplastic substrates. Filter feeding, crawling, permanent attachment, a preference for fast velocity (0.3-0.6 m/s), and coarse particle organic matter were positively correlated with the 50% macroplastic substrates. Overall, the results provided critical insights on the impact of macroplastics on the assemblage structure of biological communities by acting as suitable habitats in stream ecosystems. The study elucidated the role of traits of aquatic organisms in mediating the colonisation of plastics substrates, providing insights into the impact of plastics proliferation on riverine ecosystem functioning. Furthermore, the finding provides a baseline insight into the influence of hydraulic biotopes on the colonisation and establishment of macroinvertebrates on macroplastic acting as artificial riverine habitat.
Keywords: Macroplastics; Aquatic invertebrates -- South Africa -- Eastern Cape; Experimental ecology; Plastic scrap; Environmental degradation; Functional ecology; Biotic communities